2013
DOI: 10.1016/j.tranpol.2013.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic relationship between air transport demand and economic growth in the United States: A new look

Abstract: Keywords:Autoregressive distributed lag (ARDL) approach Economic growth Error correction model US air travel and freight demand a b s t r a c t This paper examines the short-and long-run effects of economic growth and market shocks (e.g., 9/11 terrorist attacks, Iraq war, SARS epidemic, and 2008 financial crisis) on air passenger and freight services using an autoregressive distributed lag (ARDL) approach to cointegration. Results show that, in the longrun, both air passenger and freight services tend to incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
44
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(61 citation statements)
references
References 16 publications
7
44
0
5
Order By: Relevance
“…As in previous studies [53,54,65,67], the total number of passengers (Equations (1), (3)), alongside the volume of goods transported in Europe (Equation (4)) positively influenced GDPC. Likewise, investments in airport infrastructure positively influenced economic growth (Equations (4)- (8)).…”
Section: Of 34supporting
confidence: 66%
“…As in previous studies [53,54,65,67], the total number of passengers (Equations (1), (3)), alongside the volume of goods transported in Europe (Equation (4)) positively influenced GDPC. Likewise, investments in airport infrastructure positively influenced economic growth (Equations (4)- (8)).…”
Section: Of 34supporting
confidence: 66%
“…Liu et al [26] demonstrated that the outbreak of SARS (−64.31%) influenced the loss of inbound tourists more than any other crisis event including the 1997 Asian financial crisis (−2.54%), September 11 attacks (−24.59%), the 2001 earthquake (−17.07%) in Taiwan. Chi and Baek [27] suggested that the SARS outbreak had long-term impacts on air flight demand.…”
Section: Literature Reviewmentioning
confidence: 99%
“…W krótkiej perspektywie czasowej wzrost gospodarczy oddziałuje jedynie na transport lotniczy osób. W przypadku szoków rynkowych jedynie ataki terrorystyczne 9/11 oraz epidemia SARS były przyczyną spadku popytu na transport lotniczy osób zarówno w krótkim, jak i długim okresie (Chi, Baek, 2013 ) per capita, zużycia paliwa silnikowego per capita, liczba zarejestrowanych pojazdów per capita. Autor zauważa, że istnieje długookresowa zależność przyczynowa pomiędzy popytem na transport a cenami benzyny, dochodem i wskaź-nikiem motoryzacji indywidualnej.…”
Section: Przegląd Literaturyunclassified